The Effect of Triangle Clock Needle (SJJ) Training Method on Passing Accuracy of Futsal Extracurricular Students - Trio Rizky Fauzan; Febri Wijaya (Jurnal Muara Olahraga, 2026)
This study aimed to investigate the effect of Triangle Clockwise (SJJ) training on improving passing accuracy among students participating in the futsal extracurricular program at SMP Negeri 2 Karanggayam. The study employed a quantitative approach with a one-group experimental design. A total of 15 male students were selected through purposive sampling. Passing accuracy was assessed using a standardized passing accuracy test, and the collected data were analyzed using the N-Gain test to determine the effectiveness of the training program. The results demonstrated a moderate improvement in passing accuracy, with a mean N-Gain score of 0.5481, indicating a moderately effective intervention. Furthermore, the mean passing score increased from 4.63 in the pretest to 7.31 in the posttest, representing an improvement of 2.69 points or 58.11%. These findings suggest that Triangle Clockwise (SJJ) training is an effective method for improving passing accuracy and can be recommended as a practical training strategy for futsal coaching programs at the junior high school level.